Investigating neural dynamics in autism spectrum conditions outside of the laboratory using mobile electroencephalography. (4th January 2022) - Giannadou, Aikaterini; Jones, Myles; Freeth, Megan; Samson, Andrea C.; Milne, Elizabeth
Abstract: There is currently a paucity of neuroscientific data recorded from more severely affected individuals with autism spectrum conditions (ASC). Enabling data collection to take place in a more familiar environment, that is, at home, may increase access to research participation in this group. Here, we present a new accessible method of studying brain activity of autistic individuals outside the laboratory in their home environment, using mobile electroencephalography (EEG) technology. The primary aim of the present study was to test the feasibility of acquiring good quality EEG data from autistic children at home, assessed via a set of objective data quality metrics, and to develop a list of practical guidelines on how to successfully conduct an EEG experiment in such a naturalistic setting based directly upon participants' views. To demonstrate the utility of this method, we evaluated the EEG signal quality recorded from 69 children with ASC at home using a gel‐based Eego Sports mobile EEG system. Five key indicators of data quality were assessed. Our results demonstrate that it is possible to record high quality EEG signal from children with ASC at home, generating data that could address a number of research questions. A user experience survey identified areas of good practice, which researchers should take into consideration when designing mobile EEG studies aiming to acquire data from children with ASC at a home environment. Abstract : This is the first study to demonstrate that high‐quality electroencephalography (EEG) data can be acquired from autistic children outside the laboratory in a home setting using mobile EEG technology and also the first to systematically gather data on user‐experience regarding children's participation in EEG research. Given the shift in direction toward participatory autism research, this work provides an important approach by being the first to actively explore and document the experiences of autistic individuals participating in EEG experiments.